Digitalization and resilience: Data assets and firm productivity growth during the COVID-19 pandemic - Heli Koski; Paolo Fornaro (The Research Institute of the Finnish Economy (ETLA), 2024)
This study investigates the impact of firm-level investments in data assets on productivity growth during the COVID-19 pandemic, utilizing matched employer-employee data of 13,609 Finnish firms for 2015-2020. Our estimation results indicate that firms with greater pre-pandemic investments in software and database assets and ICT experienced significantly higher labor productivity growth in the first year of the pandemic. Notably, these positive effects are predominantly observed in the service sector, while manufacturing companies did not exhibit statistically significant impacts. Furthermore, our analysis highlights that large service companies with greater investments in data assets demonstrated higher labor productivity growth than their counterparts. We also identify a noteworthy complementarity between a firm's investments in ICT and databases and employees' skills, as measured by education level. Interestingly, our empirical findings underscore that firms investing more in data, databases and ICT were statistically significantly more likely to belong to the productivity frontier of their industry.
Keywords: D22; L25; O33; 330; Data assets; Digitalization; Productivity; Growth; Resilience; Pandemics